Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Konsumen Kopi Kenangan Cabang RS Yarsi Jakarta Pusat - Muisatun; Hanuna Shafariah (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.This research was motivated by the increasing public interest in coffee drinking culture, with Kopi Kenanganas one of the popular brands. The purpose of this research was to determine the influence of ProductQuality and Price on Consumer Purchasing Decisions at Kopi Kenangan, Yarsi Hospital Branch, CentralJakarta. The sample in this research amounted to 170 respondents with a purposive sampling technique.The research was conducted using SPSS Software version 24. Data testing techniques included validitytests, reliability tests, classical assumption tests (normality, multicollinearity, heteroscedasticity), multiplelinear regression analysis, and hypothesis testing (t-test and F-test). The results showed that ProductQuality (X1) had a positive and significant influence on Purchasing Decisions (Y) with a coefficient ofdetermination (R Square) of 51.6%. Price (X2) also had a positive and significant influence with an RSquare value of 51.1%. Simultaneously, Product Quality and Price had a positive and significant influence on Purchasing Decisions, with an R-square value of 0.593. This meant that 59.3% of purchasing decisions were influenced by these two variables, while 40.7% were influenced by other factors.Keywords: Product Quality, Price, Purchasing Decisions, Kopi Kenangan